Comparison of Forsythia suspensa leaf fermented tea in the four different regions of Shanxi Province: quality, functional ingredients, and bioactivity - Li, Lijuan; Zhao, Yating; Zhang, Shu; Zhang, Xiaohong; Duan, Guofeng (Frontiers in Sustainable Food Systems, 2024)
Background Forsythia suspensa (F. suspensa) is a plant of the Oleaceae family that is used as a medicinal plant. It is a traditional Chinese medicine that functions in clearing heat and detoxification. F. suspensa contains various phytochemicals, such as lignans, flavonoids, triterpenoids, and phenylethanolic glycosides; however, the main active phytochemical in F. suspensa is phillygenin, which has lipid-lowering, antioxidant, antihypertensive, and tyrosinase inhibitory effects. However, the content of phillygenin in F. suspensa is very low, limiting its application. Methods This study used wild F. suspensa leaves (FSL) from Lingchuan County (LC), Anze County (AC), Pingshun County (PS), and Pingding County (PD) in Shanxi Province as experimental materials. Through a single factor and orthogonal experimental design, the fermentation time, temperature, and humidity of F. suspensa leaf fermented tea (FSLFT) were optimized using a black tea fermentation machine. By comparing the differences in phillygrin and phillygenin content in FSL and FSLFT, the optimal production process for increasing phillygenin content in FSLFT was sought. This study also compared the differences in bioactive substance content and in vitro antioxidant and antibacterial functions of wild FSLFT from the four counties to evaluate the quality of wild FSLFT from the four counties. Results The optimal technological parameters of Forsythia suspensa leaf fermented tea (FSLFT): fermentation time of 2 h, fermentation humidity of 80%, fermentation temperature of 35°C, the experimental results showed that the order of influence of each factor on phillygenin content was C (fermentation temperature) > A (fermentation time) > B (fermentation humidity). The cellulase activity of FSLFT was significantly higher than that of FSL (P < 0.05). The total volatile compounds of the wild FSLFT from the four counties were 87 volatile aroma components, 13 of which were common aroma components, and the PCA scores ranged from high to low as follows: AZ-FSLFT > LC-FSLFT > PS-FSLFT > PD-FSLFT. The antioxidant effects of the FSLFT were as follows: AZ-FSLFT > LC-FSLFT > PS-FSLFT > PD-FSLFT. PD-FSLFT had the least inhibitory effect on both Gram-positive and Gram-negative bacteria, whereas AZ-FSLFT had the greatest inhibitory effect. Conclusion Fermentation promoted the conversion of phillygrin to phillygenin in FSL, which might be related to the increased cellulase activity in FSL during fermentation. The AZ-FSLFT had the best quality and functional activity, which made sense given its active ingredient content. The AZ-FSLFT had the best quality and functional activity, which made sense given its active ingredient content. This study contributes to the comprehensive development and utilization of F. suspensa leaves for economic and healthcare purposes.